2011
DOI: 10.1111/j.1365-2982.2010.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of motilin on gastric distension sensitive neurons in arcuate nucleus and gastric motility in rat

Abstract: Our findings suggest that motilin neurons in Arc may accept peripheral somatosensory afferent inputs from gastric mechanoreceptors of the stomach, and also may acts as a stimulatory factor in Arc to regulate gastric motility via some inferior nucleus relay pathway. The results provide insight into the role of Arc in the control of digestion mediated via motilin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Gas O 'Dea, Brookes, & Wattchow, 2010;Shibata et al, 1995;Silkoff et al, 1988;Xu, Gao, Guo, & Sun, 2011) and were found to change after administration with diphenoxylate or water-fasting for 4 days in the present work. Gas was structured with a pair of heptadecapeptide amides and released from the astrin-containing cell (G-cell) in the antropyloric mucosa.…”
Section: Discussionsupporting
confidence: 44%
“…Gas O 'Dea, Brookes, & Wattchow, 2010;Shibata et al, 1995;Silkoff et al, 1988;Xu, Gao, Guo, & Sun, 2011) and were found to change after administration with diphenoxylate or water-fasting for 4 days in the present work. Gas was structured with a pair of heptadecapeptide amides and released from the astrin-containing cell (G-cell) in the antropyloric mucosa.…”
Section: Discussionsupporting
confidence: 44%
“…Owing to food intake, gastric volume increases, which causes distension of gastric fundus and transfer afferent information to the ARC (Xu et al . ) or LH (Jeanningros ). Excitement or inhibition of LH neurons may regulate digestive function through efferent descending signals (Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…MTL, a polypeptide secreted by Mo cells, induces strong gastrointestinal motility. By contrast, VIP, released from the inhibitory vasoactive intestinal peptidergic fibers, leads to inhibition of gastric acid secretion and relaxation of the gastrointestinal tract25262728. Thus, increasing MTL and decreasing VIP could promote gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%